Piezoelectric effect on thermoelastic Lamb waves in functionally graded plates - Wang, X.; Ren, X.; Yu, J.; Zhou, H.; Zhang, X.; Leng, J. (Archives of Mechanics, 2023)
Based on the Lord–Shulman thermoelectric elasticity theory, the piezoelectric effect on the thermoelastic Lamb wave propagation in the functionally graded material (FGM) plate is investigated. The coupled wave equations are solved by employing the Legendre polynomial series approach (LSPA), which poses the advantages of small scale of eigenvalues matrix and a convenient solution. It can directly obtain the complex wave number solutions without iteration. The obtained complex solutions, which represent the wave propagation and attenuation, are compared with those available data. Numerical examples show that the influence of gradient is profound. Results indicate that the piezoelectric effects on attenuation with the open and closed circuit condition are consistent for the S0 and S1 modes, but are inconsistent for the A0 and A1 modes. Although the piezoelectric effect is weak on the dispersion and attenuation of thermal waves, it is notable for their physical field distributions. In addition, the relaxation time is critical to electric displacements of a thermal wave mode, but is not essential for those of Lamb-like modes. The results can be used for the optimization of thermo-electric-elastic coupling structures.